The Development of Learning Device Based on Cognitive Conflict to Improve Mathematics Problem Solving Skills for Students in Madrasah Tsanawiyah - Silvia Rahayu; Ahmad Fauzan; Yerizon Yerizon; I Made Arnawa (Universitas Maritim Raja Ali Haji, 2022)
According to the National Council of Mathematics Teachers (NCTM) 2005, Mathematics is a means of problem-solving. NCTM also emphasizes that problem solving cannot be separated from learning Mathematics because problem-solving is an integral part of learning Mathematics. This study aims to improve the mathematical problem-solving ability of students in the Madrasah Tsanawiyah by using a cognitive conflict-based learning model. The subjects of this study were students of class VII Madrasah Tsanawiyah. This type of research is development research. Data collection was carried out in 3 stages, the investigation stage, the prototype phase, and the assessment phase as the level of implementation and achievement in using the cognitive conflict-based learning model. The instruments used in this study were in the form of interview guidelines, questionnaires, and observation sheets. The data analysis carried out is the analysis of data on the validity, practicality, and effectiveness of learning tools. The results of problem-solving abilities can be seen from the results of students' final tests in each meeting which always increase. Based on the study's results, it can be concluded that Cognitive Conflict-based mathematics learning tools can improve students' mathematical problem-solving abilities.